Land and Sea: Maritime Capitalism, Terrestrial Frontiers and Their Literary Mediations in Nineteenth‐Century Argentina. - Aguayo‐Borquez, Claudio (Bulletin of Latin American Research, 2025)
This paper grapples with two crucial landscapes of extraction of the Argentine nineteenth century and their mediation through literature: maritime capitalism and primitive accumulation. First, it describes Domingo Faustino Sarmiento's aquatic utopia, focusing on his Americanism, his equation between oceans and plains and the aporias of his Orientalism. Second, this study shows an early displacement towards countryside provincialism in Argentine ideology by analysing José Mármol's novel Amalia. Departing from Etienne Balibar's concept of interior frontiers, this paper shows the emergence of a terrestrial imagination that was crucial for the consolidation of telluric ideologies. This process of ideological displacement coincides with the vanishing frontier and the dissolution of gaucho life within the Argentinian landscape, enabling the emergence of a new contempt for the urban plebs and the proletariat.